Study of the internal didactic transposition of the concept of reasoning by mathematical induction in Tunisian secondary education - Walid Soltani,; Chellougui Faïza, (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2025)
This paper focuses on the teaching of reasoning by mathematical induction in Tunisian secondary schools. The main objective is to analyse mathematics teachers' knowledge of this fundamental concept and how they approach it in the classroom. The study reveals several significant findings, among which is the often-superficial presentation of this reasoning in the curriculum. This limited approach has an impact on the effective transmission of this complex concept to learners.